Polyphosphates as inhibitors of surface mould growth on hard cheese during ripening - Suárez, Viviana Beatriz (2012)
A novel treatment using polyphosphates to protect cheeses against superficial mould growth was assayed. The treatments were: control commercial paint with natamycin (I), commercial paint based on polyvinyl?water (II), immersion in a saturated solution of polyphosphate (III), immersion and commercial paint (IV), commercial paint of polyphosphate solutions (V) and immersion and commercial paint of a saturated solution of polyphosphates (VI). The cheeses were ripened for 6 months. Superficial mould growth was inhibited in groups IV and VI when compared to cheeses from the control group (I). Statistical sensory analysis made between cheeses from groups IV and I (control) showed no significant differences.